Exploring the relationship between church worship, social bonding and moral values. (March 2022) - Brown, Jennifer E; van Mulukom, Valerie; Jong, Jonathan; Watts, Fraser; Farias, Miguel
Religion is often understood to play a positive role in shaping moral attitudes among believers. We assessed the relationship between church members' levels of felt connectedness to their respective congregations and perceived similarity in personal and congregational moral values, and whether there was a relationship between these and the amount of time spent in synchronous movement or singing during worship. The similarity between personal and perceived congregational moral importance (the importance assigned to different moral items) was correlated with feelings of closeness to one's congregation but not by the amount of time spent in synchronous movement or singing. Differences in moral foundations scores and in moral importance of specific issues were found between different theological traditions. These findings demonstrate that, for churchgoers, there is a relationship between the use of music or synchronous movement in a church service and feelings of social bonding and there is also a relationship between the degree to which churchgoers identify with their church community and the degree to which they believe their priorities match those of their church. Furthermore, differences in theological tradition appear to be reflected in differences in moral values.